Plagiarisme Karya Arsitektur dalam Perspektif Etika Profesi dan Kaidah Tata Laku Profesi Arsitek - Pahlawan, Muhamad Reiza; Sunaryo, Rony Gunawan; Hariyanto, Agus Dwi (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2025)
Title: Plagiarism of Architectural Works from the Perspective of Professional Ethics and the Code of Conduct for Architects Plagiarism in the creative and academic world is a serious issue related to intellectual property rights violations, including in the field of architecture. Law No. 28 of 2014 concerning Copyright protects architectural works as part of copyright, while the code of professional ethics formulated by the Indonesian Architects Association (IAI) regulates ethical aspects in architectural practice. However, until now there have been no clear parameters to determine whether an architectural work can be categorized as plagiarism. This study examines the issue of plagiarism in architecture from the perspective of the code of ethics and rules of conduct for the architectural profession in Indonesia. The method used is a qualitative-interpretive approach with an analysis of literature studies and a study of regulations and cases of architectural plagiarism in Indonesia. The results of the study show that Law No. 28 of 2014 has guaranteed copyright protection, and the code of ethics for the architectural profession has regulated general ethical principles. However, there are no explicit boundaries that distinguish between inspiration and plagiarism in architectural works. This research is expected to be the basis for formulating clearer regulations in determining plagiarism in architecture.